2016
DOI: 10.1049/iet-pel.2015.0857
|View full text |Cite
|
Sign up to set email alerts
|

Ripple‐reduced model predictive direct power control for active front‐end power converters with extended switching vectors and time‐optimised control

Abstract: Model predictive control (MPC) is an attractive technique for power electronics and drives. It requires no extra modulators and considers the non-linear nature of the power converter, so remarkable control performance can be achieved. However, since the conventional MPC scheme uses only one switching state during the whole control interval, ripples of the control variables are more evident than that of the classical modulator based techniques. This study proposed a ripple-reduced model predictive direct power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…According to the third line and the last line of Table I, the direction of io_in caused by V2 is opposite to that caused by V3, but these two vectors have the same direction of the output voltage, which means that the line current can track the line current with the same trend, but the movement of the capacitor voltage error is opposite by using V2 and V3, Therefore, V2 and V3 are a pair of redundant vectors for neutral-point voltage balancing. The same conclusion can be gotten for V 5 and V 6 .…”
Section: B Voltage Balancingsupporting
confidence: 74%
“…According to the third line and the last line of Table I, the direction of io_in caused by V2 is opposite to that caused by V3, but these two vectors have the same direction of the output voltage, which means that the line current can track the line current with the same trend, but the movement of the capacitor voltage error is opposite by using V2 and V3, Therefore, V2 and V3 are a pair of redundant vectors for neutral-point voltage balancing. The same conclusion can be gotten for V 5 and V 6 .…”
Section: B Voltage Balancingsupporting
confidence: 74%
“…There is not any PI or hysteresis controller in the proposed strategy compared with DPC and VOC. It provides a better dynamic response to the load variations (five cycles) than other predictive method proposed in Ma et al, Monfared et al, Song et al, and Fang et al 9,18,30,39 The proposed PPC has the more straightforward theory than the other strategies because of using some simple approximations. It observed that the converter has lower current harmonic distortion (<2%) than the proposed method in Ma et al, Monfared et al, and Song et al 9,18,30 The input current is sinusoidal.…”
Section: Discussionmentioning
confidence: 99%
“…It has constant output voltage with only 6% voltage ripple. It provides a better dynamic response to the load variations (five cycles) than other predictive method proposed in Ma et al, Monfared et al, Song et al, and Fang et al 9,18,30,39 The proposed PPC has the more straightforward theory than the other strategies because of using some simple approximations. It reveals that using three-level SVM for single-phase NPC rectifier makes this algorithm interesting for digital implementation.…”
Section: Discussionmentioning
confidence: 99%
“…where λ represents the weighting factor, P ref (k) and Q ref (k) are the instantaneous reference powers at the kth switching interval. For the equal importance of active power and reactive power, the weighting factor λ = 1 [27]. The cost function (22) is relative to the variable U z (k), in order to gain the minimum J(k), U z (k) needs to satisfy dJ k dU z k = 0…”
Section: Optimal Elliptical Radius Of U Ab Terminal Trajectorymentioning
confidence: 99%